ANALISIS WACANA KRITIS PENDEKATAN TEUN A. VAN DIJK TERHADAP BERITA “PMK MEWABAH, MUI JATENG BEBERKAN SYARAT SAH HEWAN KURBAN” - Dinni Sukma Haryanti; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Towards the celebration of Eid al-Adha in 2022, there was a lot of discussion in the media, both print and online, about the outbreak of Foot and Mouth Disease (FMD) in livestock. The purpose of this research is (1) to describe the text structure of the news according to the critical discourse analysis approach by Teun A. Van Dijk, and (2) to describe the characteristics of critical discourse analysis in the news text. This study employed a qualitative descriptive research method using Teun Van Dijk's Critical Discourse Analysis model. The data source for this research was a news article titled "Critical Discourse Analysis using Teun A. Van Dijk's Approach on the News 'FMD Outbreak, Central Java MUI Reveals Conditions for Valid Sacrificial Animals'" published on jatengprov.go.id (Central Java Provincial Government Public Relations and Protocol Office) in June 2022. The data collection technique involved reading and note-taking. The data analysis used in this research was qualitative data analysis using an interactive model. The analysis process consisted of three steps: (1) data reduction, (2) data presentation, and (3) verification or conclusion. These three steps of data analysis were interconnected and had a sequential relationship. The results of the research showed that (1) the text structure of the news aligned with Van Dijk's theoretical structure, which includes macro structure, supra-text structure, and micro-text structure, and (2) based on the characteristics of critical discourse analysis, such as action, context, history, power, and ideology, several opinions in the newspaper text writing could be influenced. Keywords: Discourse analysis, Foot and Mouth Disease, Teun A. Van Dijk.